2006
DOI: 10.1002/jcu.20301
|View full text |Cite
|
Sign up to set email alerts
|

Doppler sonography evaluation of flow velocity and volume of the extracranial internal carotid and vertebral arteries in healthy adults

Abstract: Purpose. To measure with Doppler sonography the velocity and volume of blood flow in the extracranial internal carotid artery (ICA) and vertebral artery (VA) of healthy adults and to calculate total cerebral blood flow volume (tCBFV).Methods. Bilateral ICA and VA were examined sonographically in 180 healthy adults. Angle-corrected peak systolic (Vps), end-diastolic (Ved), and time-averaged maximum blood flow velocity (TAV) were measured in pulsed Doppler mode, and the resistance index (RI) and pulsatility inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 24 publications
5
50
0
2
Order By: Relevance
“…The acquired values of blood velocity, PI, and RI are in good accordance with Doppler sonography measurements reported in the literature. 29 In the present study, a 2D-PC sequence with multidirectional velocity-encoding and high spatial resolution was chosen to accurately capture blood flow of both vertebral arteries within a single measurement. A lower temporal resolution was taken into account to achieve this.…”
Section: Discussionmentioning
confidence: 99%
“…The acquired values of blood velocity, PI, and RI are in good accordance with Doppler sonography measurements reported in the literature. 29 In the present study, a 2D-PC sequence with multidirectional velocity-encoding and high spatial resolution was chosen to accurately capture blood flow of both vertebral arteries within a single measurement. A lower temporal resolution was taken into account to achieve this.…”
Section: Discussionmentioning
confidence: 99%
“…As the PI and RI are known to reflect resistance distal to the measurement point (14,15), results indicated that DHCA with RCP, but not regular CPB without DHCA, increases the resistance of cerebral vessels distal to the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…The peak systolic velocity (PSV), end-diastolic velocity (EDV), and mean velocity (MV) were measured using pulsedwave Doppler ultrasound (12,13). The pulsatility index (PI) and resistance index (RI) are known to reflect vascular resistance distal to the position where the Doppler signal is received (14,15). PI is calculated as (PSV-EDV)/MV and RI as (PSV-EDV)/PSV.…”
Section: Introductionmentioning
confidence: 99%
“…According to findings in non-pregnant women, vessel diameter in our study was equal for the right and left CCAs, but larger on the left side for the VA, suggesting left dominance in the posterior circulation [9,10,12]. A large retrospective study involving 1,000 individuals performed by Chen et al [11] analyzed vertebral hypoplasia and its possible relation to decreased net flow volume through the VAs.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is part of a broader project studying maternal cerebral circulation in normal pregnancy that will ultimately establish reference values in pregnancy for different Doppler indices for the common and internal carotid arteries (ICAs), as well as the VAs. Several groups have evaluated these vessels in non-pregnant populations [9,10,11,12]. Although the carotid vessels do not appear to differ based on side, the right and left VAs do differ in diameter and flow, which may potentially influence our reference chart.…”
Section: Introductionmentioning
confidence: 99%